Ceramic Coatings Applications in Engineering - Shi, Feng (IntechOpen, 2012)
The main target of this book is to state the latest advancement in ceramic coatings technology in various industrial fields. The book includes topics related to the applications of ceramic coating covers in enginnering, including fabrication route (electrophoretic deposition and physical deposition) and applications in turbine parts, internal combustion engine, pigment, foundry, etc.